Fewer Community-Acquired Colds with Daily Consumption of Lactiplantibacillus plantarum HEAL9 and Lacticaseibacillus paracasei 8700:2. A Randomized, Placebo-Controlled Clinical Trial - Ahrén, Irini Lazou (J Nutr, 2020)
BACKGROUND: Viral infections of the upper airways are the most common cause for absence from work or school, and there is evidence for probiotic efficacy in reducing the incidence and severity of these infections. OBJECTIVES: We aimed to confirm the previously reported beneficial effects of Lactiplantibacillus plantarum HEAL9 and Lacticaseibacillus paracasei 8700:2 against community-acquired common colds and identify a possible mechanism of action. METHODS: In a double-blind study, healthy adults (18–70 years of age) with at least 4 colds during the last 12 months before recruitment were randomly allocated to consume either probiotics (n = 448; total daily dose of 10(9) CFU with the 2 strains equally represented) or placebo (n = 450) once daily for 12 weeks. Recruitment took place from October to February during 2013–2016 (over 3 cold seasons). The probiotic impact on the severity of the colds (Wisconsin Upper Respiratory Symptom Survey−21) was the primary endpoint, whereas secondary endpoints included the incidence rate and duration of colds and an analysis of immune markers. Mann-Whitney U test and mixed model were used for the analysis of continuous variables and Fisher´s exact test was used for the analysis of categorical endpoints. RESULTS: Symptom severity was not reduced after intake of the probiotic, despite the positive trend seen in the first season. However, significantly fewer colds were experienced in the probiotic group (mean of 1.24 colds) as compared to the placebo group (mean of 1.36 colds; P = 0.044) for subjects reporting at least 1 cold, the incidence of recurring colds was 30% lower (20.8% vs. 29.8%, respectively; P = 0.055), and the use of analgesics was 18% lower (26.3% vs. 32%, respectively; P = 0.07). After 12 weeks, the change from baseline for IFN-γ differed between the groups (mean difference of −7.01; 95% CI, −14.9 to 0.93; P = 0.045). CONCLUSIONS: Intake of Lactiplantibacillus plantarum HEAL9 and Lacticaseibacillus paracasei 8700:2 can be protective against multiple colds in adults prone to getting colds. This trial was registered at clinicaltrials.gov as NCT02013934.